High visibility colored fabrics for normal trichromats and individuals with color vision defects in a sunset-simulated environment. - Tatsuya Iizuka; Takushi Kawamorita; Hajime Tsuji; Hiroyuki Kanai; Toshihiro Hirai; Hiroo Suzuki; Tomoya Handa; Hitoshi Ishikawa (PLoS ONE, 2022)
This study aimed to investigate the visibility of colors in congenitally color vision defect people using general and fluorescent colors in an environment simulating sunset to examine the standards for high-visibility safety clothing for general users. Twenty participants with normal trichromats, seven protanopes, and five deuteranopes were included, with mean ages (± standard deviation) of 21.0±1.0, 46,7±16.1, and 56.6±6.9 years, respectively. Dyed fabrics were used to evaluate visibility. We evaluated brightness and conspicuousness sensitivity by combining red, yellow-red, yellow, green, red-purple, blue, white, black, fluorescent yellow, and fluorescent orange. For brightness sensitivity, the combination of fluorescent yellow and white/yellow stripes was highly visible and significantly different from all other samples (p < 0.05). For conspicuousness sensitivity, the combinations of black/fluorescent yellow, black/yellow, black/white, black/yellow-red, and white/red-purple stripes were highly visible and significantly different from all the other samples (p < 0.05). Yellow light is most visible and even better when fluorescent. They are based on specific spectral sensitivity, and yellow is the most visible, even for congenitally colorblind individuals. Furthermore, with regard to color combinations, it was found that the contrast between two distinct light or dark colors, such as black, yellow, black, and white, is perceived to be equally noticeable by congenital color vision defect individuals. This suggests the possible further applications of safety clothing.